2016
DOI: 10.1103/physreva.93.063863
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic optical bistability in a strongly driven Rydberg ensemble

Abstract: We observe and characterize intrinsic optical bistability in a dilute Rydberg vapor. The bistability is characterized by sharp jumps between states of low and high Rydberg occupancy with jump up and down positions displaying hysteresis depending on the direction in which the control parameter is changed. We find that the shift in frequency of the jump point scales with the fourth power of the principal quantum number. Also, the width of the hysteresis window increases with increasing principal quantum number, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 38 publications
1
35
1
Order By: Relevance
“…One interesting aspect observed in recent anti-blockade experiments using a full counting analysis is a bimodal excitation number distribution [27,28] and a hysteresis in the excitation dynamics [13,17]. It has been under debate whether this indicates a transition to a bistable steady state of the open many body system [8,9,13,16,29,30].…”
Section: Introductionmentioning
confidence: 99%
“…One interesting aspect observed in recent anti-blockade experiments using a full counting analysis is a bimodal excitation number distribution [27,28] and a hysteresis in the excitation dynamics [13,17]. It has been under debate whether this indicates a transition to a bistable steady state of the open many body system [8,9,13,16,29,30].…”
Section: Introductionmentioning
confidence: 99%
“…δ p = −δ c , result from the expected off-resonant EIT in combination with the lensing effect. Generally, asymmetries in EIT line shapes are attributed to Rydberg interactions or super radiance [5,6,12,15,23,25] but our model indicates that micro lensing has a considerable effect. With the chosen Rydberg state, 29S 1/2 , we also minimize the possibility of significant interactions which makes our technique suitable for the line shape studies.…”
mentioning
confidence: 57%
“…However, the model also has a maximum Rabi frequency for which bistability can be present, a result that has not yet been observed in the lab. A systematic study of the critical point with changing Rydberg state was made, and we found that the critical detuning follows the form ∆ c R ∝ (n − δ) α where n is the principal quantum number, δ is the quantum defect and we measure α = 3.8 ± 0.3 ( Figure 5.3) [103]. Using this result, phenomenological formulas for Γ and V ,…”
Section: Steady State Phase Mapmentioning
confidence: 72%
“…Alkali metal atomic vapours excited to high lying Rydberg states exhibit intrinsic optical bistability which has been the subject of several recent studies [42,43,103,104].…”
Section: Bistabilitymentioning
confidence: 99%